2021
DOI: 10.1002/masy.202000310
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Assessment Methods Enhanced by IoT and Simulation Tools

Abstract: The advent of Industry 4.0 (I4.0) principles and technologies has been a great boost for manufacturing companies, constantly focused on the production processes optimization in order to reach the double objective of improving productivity and minimizing related costs. Today, the use of I4.0 technologies seems to be more accessible for a large number of companies, allowing to perform a more detailed analysis on their processes by means of experimental data coming directly from the system. In this context, ergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In order to realize the refined channel environment simulation, it is necessary to establish a signal waveform prediction model with good sea area adaptability, accuracy and real-time, especially the accurate simulation of the marine level nonuniform environment. (2) In actual simulation, it is necessary to put multiplatforms, multisensors, and multiweapons under unified space-time conditions. It is not only necessary to solve the coupling problem of environment, sensors, and weapons, but also to solve the different space-time granularity and space-time coupling problem of engagement-level simulation and signal-level simulation.…”
Section: Design Ideamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to realize the refined channel environment simulation, it is necessary to establish a signal waveform prediction model with good sea area adaptability, accuracy and real-time, especially the accurate simulation of the marine level nonuniform environment. (2) In actual simulation, it is necessary to put multiplatforms, multisensors, and multiweapons under unified space-time conditions. It is not only necessary to solve the coupling problem of environment, sensors, and weapons, but also to solve the different space-time granularity and space-time coupling problem of engagement-level simulation and signal-level simulation.…”
Section: Design Ideamentioning
confidence: 99%
“…e use setting of the virtual experiment platform is designed by the designer according to the experience of teachers and will remain unchanged for a certain period of time. However, in the teaching process, it is found that with the continuous development of technology, the problems existing in students' learning process will change over time, which is not eternal [1,2]. (2) e virtual experiment platform can only record students' experiments, not the experimental process, which makes teachers unable to effectively understand the problems existing in the process of students' experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to this comprehensive integration that enables the communication between humans and machines, insight and data-driven solutions for complicated operation problems are available [2]. As a result, the so-called intelligent manufacturing system can be monitored in such an efficient way [3], with optimized resources regarding human labor [4], production time [5], energy [6], and operational cost [7]. With these useful applications, modern machines nowadays come with various ways of transmitting data and communicating with each other as well as to the system [8], creating a connected Cyber-Physical Production System (CPPS) [9].…”
Section: Introductionmentioning
confidence: 99%